Monoclonal antibodies in the management of rheumatoid arthritis - Isaacs, John (Henry Stewart Talks, 2007)
Background to rheumatoid arthritis, Rheumatoid arthritis pathogenesis, Aims of therapy in rheumatoid arthritis, Targeting T-cells with depleting monoclonal antibodies, Non-depleting therapies that target T-cells, Targeting B-cells in rheumatoid arthritis, Co-stimulation blockade, Targeting the interleukin-6 receptor
Reviewed at 2019/11/26